Blink Reflex study in Patients with Migraine (Iraqi Journal of Medical Sciences, 2022)
Background: The pathogenesis of migraine is thought to include activation of the trigeminovascular system. The blink reflex (BR) test is a well-known method of studying the trigeminal system.Objective: To look into the differences in BR response in migraine patients using the standard approach and to compare the results with matched control subjects, looking for a possible difference in BR ictally and interictally, and clarify whether migraineurs with aura differ from those without aura.Methods: A case-control study of 80 subjects; 40 patients were diagnosed with migraine, with or without aura, and 40 matched healthy volunteers. Disease duration ranges from 2 to 82 months. Both groups were submitted to medical history, clinical neurological examination, and binocular BR study of both eyes.Results: BR data were not different between male and female patients. Right cR2 latency and left iR2 were prolonged in the migraineurs group patients. Right iR2 and cR2 latencies recorded interictally were longer than those obtained ictally. No difference was observed between those with and without aura. The pain location side is not associated with the stimulation side.Conclusion: Patients suffering from episodic migraine may have altered interneuronal brainstem circuits. BR data would not change whether migraine was with or without aura. Interictal changes in BR suggest trigeminovascular dysfunction in migraineurs patients is not a transient phenomenon.Keywords: Migraine, Blink ReflexCitation: Esmael ZF, Hamdan FB. Blink reflex study in patients with migraine. Iraqi JMS. 2022; 20(2): 175-182. doi: 10.22578/IJMS.20.2.3
Keywords: Migraine; Blink Reflex